Developing Teacher Teaching Skills Using the Snowball Throwing Learning Model at Midang 3 State Elementary School - Zarwatun, Laela (Asian Journal of Applied Education (AJAE), 2023)
In this research, the research approach used is Classroom Action Research (PTK) with a test data collection method to obtain data about students' reading abilities after learning the Snowball Throwing Model (ST), a questionnaire method to obtain data on the teacher's level of success in implementing the Snowball Throwing Model (ST) learning. ) in the Indonesian language subject reading material, while the observation method is applied when the teacher designs and applies Snowball Throwing (ST) Model learning in learning activities. Data analysis in this research is to fully apply data analysis in PTK, namely through discussion of criteria, scope of research, and visible behavior. Meanwhile, data validity is achieved in three ways, namely extended observation, triangulation (data triangulation, method triangulation and theory triangulation), and discussion with colleagues. Data shows that when teachers teach Indonesian reading material without carrying out class actions in Class IV of Midang 3 State Elementary School, Gunungsari District, West Lombok, the average class score obtained by students is below the Minimum Completeness Criteria score (7.0) where the Minimum Completeness Criteria for Indonesian is 7.5. Meanwhile, after carrying out class actions by applying the Snowball Throwing (ST) Model of learning, the average class score obtained by students was above the Minimum Completeness Criteria (KKM) score, namely 7.6.